Amiodarone-induced thyrotoxicosis in a pediatric patient: A rare and demanding clinical case - Sofia Oliveira; Bernardo Marques; Sérgio Laranjo; Lurdes Lopes (MDPI AG, 2019)
Thyroid dysfunction is one of the most common adverse effects of amiodarone therapy, ranging from subclinical changes to overt clinical thyrotoxicosis (AIT) and/or hypothyroidism. Due to its heterogeneity, AIT lasts as a defiant entity, leading to a thorny treatment course, particularly in pediatrics. AIT can be classified as either type 1, type 2 or mixed form based on its pathophysiology. Differentiating between the main AIT subtypes is quite relevant, since there is specific treatment for both, however, this distinction may be difficult in clinical practice. We describe a rare case of AIT in a pediatric patient, with an uncommon congenital cardiac malformation, that started amiodarone therapy due to paroxysmal supraventricular tachycardia. AIT was reported 26 months after drug onset, with a sudden and explosive emerging. This case highlights the current AIT management challenges on the highdemanding pediatric field pursuing, ultimately, an enhanced patient´'s care.